Feasibility and Acceptability of Antenatal Hepatitis C Screening: A Pilot Study - Joseph Valamparampil; Jaswant Sira; Maxine Brown; Saket Singhal; Deirdre Kelly (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Hepatitis C virus (HCV) is not currently included in the United Kingdom routine antenatal screening program, but the latest guidelines from the Centers for Disease Control and Prevention, American Association for the Study of Liver Diseases, and Infectious Diseases Society of America recommend HCV screening for all pregnant women during each pregnancy. The aim of this study was to collect qualitative data on the feasibility and acceptability of antenatal HCV screening in pregnant women at the time of routine antenatal screening at 12 weeks, to estimate patient knowledge about HCV and identify the prevalence of HCV infection in antenatal women. Methods. This was a pilot study targeting a single hospital-based antenatal clinic in Birmingham, initially conducted for eight weeks with a further extension of the study period to enhance recruitment to meet the feasibility target of 500 patients. Data collected included demographic and epidemiological details. Pregnant women attending the antenatal unit were given information regarding HCV and antenatal screening for HCV prior to their initial antenatal visit. During the antenatal visit, research nurses provided further information about the study and HCV infection. Consent was obtained for taking part in the study and testing for HCV using blood samples taken at the same time as other routine antenatal screening blood tests. All women who agreed to participate in the study were asked to complete an acceptability and knowledge questionnaire. All women had HCV antibody testing as the primary screening assay. The test result was communicated in writing to the women and their general practitioner. Confirmatory positive antibody tests were followed up with quantitative HCV PCR and genotype analysis. The outcomes of testing were no evidence of HCV infection and evidence of past HCV infection or current HCV infection. Results. Five hundred and forty-nine women were approached in the antenatal clinic; 30 women refused consent while 29 women were excluded from the study (blood tests not performed after consenting, age less than 18 years, and consent form lost). Four hundred and ninety women were included in the study. The median age of the study population was 29 years (range, 18–46). Knowledge about blood-borne viruses was limited; 75% of women had some understanding about antenatal hepatitis B (HBV) and human immunodeficiency virus (HIV) testing. Previous awareness about hepatitis C was reported by 55%. Ninety-one percent of women found the information they were given about hepatitis C helpful. Ninety-six percent of the women included in this study found the counselling they received about HCV useful and felt that the delivery of this information was carried out in an acceptable manner. Once given information about HCV, 99% felt that universal screening for HCV should be implemented. HCV antibody was negative in 489 women. One patient with a positive HCV antibody (prevalence: 0.2%) had a negative HCV PCR. Conclusion. Routine antenatal screening for HCV is not currently recommended in the UK. Our study suggests that antenatal HCV screening would be both feasible and acceptable to most pregnant women attending antenatal clinics. Though the awareness of HCV was low, with appropriate counselling and communication, 99% of pregnant women were in favor of antenatal screening for HCV. Antenatal screening would identify HCV-positive mothers and allow follow-up of their infants so that any infected mothers and infants could be offered effective curative therapy and prevent the progression of liver disease. The inclusion of HCV antenatal screening would complete the blood-borne virus profile and enhance the WHO target to eliminate HCV in the UK.